Comparison of the alendronate and irradiation with a light-emitting diode (LED) on murine osteoclastogenesis. Issue 1 (January 2017) - Sohn, Hong; Ko, Youngjong; Park, Mineon; Kim, Bora; Park, Jung; Kim, Donghwi; Moon, Young; Lim, Wonbong
Abstract Photomodulation therapy (PBMT) using light-emitting diode (LED) has been proposed as an alternative to conventional osteoporosis therapies. Our aim was to determine the effect of irradiation with a light-emitting diode on receptor activator of NF-κB ligand (RANKL)-mediated differentiation of mouse bone marrow macrophages into osteoclasts and compare it to alendronate treatment. The cells were irradiated with LED at 635±10 nm, 9-cm spot size, 5 mW/cm2, and 18 J for 60 min/day in a CO2 incubator. The differentiation of irradiated and untreated RANKL-stimulated bone marrow macrophages into osteoclasts was evaluated by tartrate-resistant acid phosphatase (TRAP) staining and by molecular methods. These included assessing messenger RNA (mRNA) expression of osteoclastic markers such asTRAP, c-Fos, Atp6v0d2, DC-STAMP, NFATc1, cathepsin K, MMP9 andOSCAR ; phosphorylation of various MAPKs, including extracellular signal-regulated kinase ERK1/2, P38, and JNK; NF-κB translocation; and resorption pit formation. Results were compared to those obtained with sodium alendronate. Production of reactive oxygen species was measured by a 2', 7'-dihydrodichlorofluorescein diacetate assay. LED irradiation and alendronate inhibited mRNA expression of osteoclast-related genes, such asTRAP, c-Fos, andNFATc1, and reduced the osteoclast activity of RANKL-stimulated bone marrow macrophages. LED irradiation, but not alendronate, also inhibited the production of reactive oxygen species (ROS); phosphorylation of ERK, P38, and IκB; and NF-κB translocation. These findings suggest that LED irradiation downregulates osteoclastogenesis by ROS production; this effect could lead to reduced bone loss and may offer a new therapeutic tool for managing osteoporosis.